2010
DOI: 10.1680/warm.2010.163.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Using recycled waste tyres in concrete paving blocks

Abstract: There is general agreement that waste tyres should be better managed in order to preserve valuable resources and prevent environmental damage as a result of improper disposal. This paper describes the use of crumb rubber in concrete paving blocks. Existing block material is characterised as a composite with high compressive strength but with low toughness; the addition of rubber improves toughness while meeting minimum strength requirements. A total of 4300 rubberised concrete paving blocks were produced in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…This is due to the lower relative density of CRC than plain concrete with natural aggregates which has been previously observed [7,9,13,24,29] particularly when fine aggregates were replaced. CRC also has higher air contents than plain concrete [25,44] which is confirmed here by the increased density of the 7.5% fine aggregate replacement CRC's for every crumb rubber grade used. This reduced weight is desirable in a number of architectural applications including facades, precast elements and in concrete toppings on metal decks [43,46].…”
Section: Densitysupporting
confidence: 66%
See 1 more Smart Citation
“…This is due to the lower relative density of CRC than plain concrete with natural aggregates which has been previously observed [7,9,13,24,29] particularly when fine aggregates were replaced. CRC also has higher air contents than plain concrete [25,44] which is confirmed here by the increased density of the 7.5% fine aggregate replacement CRC's for every crumb rubber grade used. This reduced weight is desirable in a number of architectural applications including facades, precast elements and in concrete toppings on metal decks [43,46].…”
Section: Densitysupporting
confidence: 66%
“…It is reported that over 80% of all asphalt in the state contains rubber asphalt accounting for roughly 12 million endof-life tyres [24]. Research [25] has shown that the sound absorption qualities of asphalt are significantly improved over time with the inclusion of crumb rubber in lightweight pavements due to greater energy absorption despite the well published reductions in compressive and tensile strength. This is supported by other work [26][27][28] who found the levels of vibration damping were 230%…”
Section: Crc Acoustic Propertiesmentioning
confidence: 99%
“…Since the production of shredded rubber does not require any sophisticated machineries or instrumentation techniques, the reuse of scrap rubber in concrete leads to both environmental and economic advantages. This additive has proved to be of great significance as a means to improve concrete properties such as resistance to abrasion, shock and vibration absorption and ductility and also to reduce the use of conventional materials in the concrete matrix along with recycling of waste rubber tyres [12][13][14][15][16][17]. Thus, the development of rubberized concrete was a major move towards achieving sustainable concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Among the undesirable effects created are noise pollution and poor riding quality. Many researches have been done on the physical and mechanical properties of different types and design of concrete paving block [2][3][4]. These initiatives were taken in order to widen the usage and improve the performance of CPB.…”
Section: Introductionmentioning
confidence: 99%